Scrutinizing interlaminar fatigue loading cycle in composites using acoustic emission technique: Stress ratio influence on damage formation - Ferreira Motta, Roberto [UNESP]; Alderliesten, René; Yutaka Shiino, Marcos [UNESP]; Odila Hilário Cioffi, Maria [UNESP]; Jacobus Cornelis Voorwald, Herman [UNESP] (Elsevier, 2020)
Current models for delamination propagation prediction in fiber-reinforced polymer (FRP) composites exhibit limitations to explain the physics underlying the mechanisms of damage formation in fatigue. In order to contribute in this field, this research focuses on the study of damage development within a single loading cycle of FRP double cantilever beam specimens under different stress ratios (R). The acoustic emission technique was used to investigate damage propagation. Results showed that under high R-ratios, the load cycle spends an increased time above the threshold energy (Uth). This time difference affects the damage distribution within a single loading cycle. Furthermore, the steady-state delamination propagation was influenced by the R-ratio variation due to the modification of the external work applied to the specimen.
Keywords: Acoustic emission; Delamination; Fatigue; Laminates